Developing The Entrepreneurial Spirit of Santri (Gen Z): Challenges And Strategies - Mawaddatul Ulya; Muhammad Fajrul Khairullah (LP2M IAIN Palopo, 2024)
Generation Z, born between 1997 and 2012, represents a new generation with unique characteristics that distinguish them from previous generations. They are known as digital natives, cerative individuals, and prosses a high entrepreneurial spirit. In Indonesia, “santri” are a group of young people with the potential to develop their entrepreneurial spirit. This research aims to analyze the development of the entrepreneurial spirit among santri (Gen Z) at Pondok Modern Tazzaka, focusing on the challenges and startegies faced. The research method used is qualitative with data collection techniques including interviews, observations, and document studies. The results show several challenges in developing the entrepreneurial spirit of santri at Pondok Modern Tazzaka, namely : 1) Lack of structured entrepreneurship curriculum and programs; 2) Limited access to capital and informations; 3) A santri culture that is more focussed on religious studies ; 4) Lack of guidance and mentoring from entrepreneurs. Strategies that can be implemented to overcome these challenges are : 1) Developing a structured and comprehensive entrepreneur curriculum and programs; 2) Improving access to capital and information for santri; 3) fFostering an entrepreneurial culture within the pesantren environment; 4) Strengthening guidance and mentoring from entrepreneurs.